Updated Topics in Minimally Invasive Abdominal Surgery - AbdelRaouf ElGeidie, Ahmed (IntechOpen, 2011)
Updated topics in minimally invasive abdominal surgery provides surgeons interested in minimally invasive abdominal surgery with the most recent techniques and discussions in laparoscopic surgery. This book includes different topics covering a big variety of medical conditions with up-to-date information. It discusses many controversies in a clear and user-friendly manner. This book is made for young junior surgeons in training and also senior surgeons who need to know the most recent work in the field of laparoscopy. To make the material easily digestive, we provided the book with many figures and illustrations for different procedures and technical pearls.